2012
DOI: 10.1111/j.1460-9568.2012.08220.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐132 regulates recognition memory and synaptic plasticity in the perirhinal cortex

Abstract: Evidence suggests that the acquisition of recognition memory depends upon CREB-dependent long-lasting changes in synaptic plasticity in the perirhinal cortex. The CREB-responsive microRNA miR-132 has been shown to regulate synaptic transmission and we set out to investigate a role for this microRNA in recognition memory and its underlying plasticity mechanisms. To this end we mediated the specific overexpression of miR-132 selectively in the rat perirhinal cortex and demonstrated impairment in short-term recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 39 publications
4
79
0
Order By: Relevance
“…A link between miR-132 expression and cognition has also been established. Transgenic overexpression of miR-132 in the forebrain impaired recognition memory (Hansen et al, 2010;Scott et al, 2012). In contrast, induced expression of endogenous miR-132 in response to a spatial memory task enhanced cognition (Hansen et al, 2013), suggests that the expression level of miR-132 is tightly regulated to control learning and memory (Bicker et al, 2014).…”
Section: Mirnas In Neurodevelopmentmentioning
confidence: 93%
See 1 more Smart Citation
“…A link between miR-132 expression and cognition has also been established. Transgenic overexpression of miR-132 in the forebrain impaired recognition memory (Hansen et al, 2010;Scott et al, 2012). In contrast, induced expression of endogenous miR-132 in response to a spatial memory task enhanced cognition (Hansen et al, 2013), suggests that the expression level of miR-132 is tightly regulated to control learning and memory (Bicker et al, 2014).…”
Section: Mirnas In Neurodevelopmentmentioning
confidence: 93%
“…Regulate pain behavior Pan, et al, (2014) CaMKIIγ Associated with Scz through regulating NMDA receptor signaling Kocerha, et al, (2009) Associated with Scz and BP as revealed by elevated expression in these patients Beveridge, et al, (2010), Smalheiser, et al, (2014) miR-132 p250GAP Promote dendritic development Impey, et al, (2010), Pathania, et al, (2012), Wayman, et al, (2008) MeCP2 Regulate dendritic morphology Klein, et al, (2007) Mediate the integration of newborn neurons Luikart, et al, (2011) Regulates synaptic plasticity & recognition memory Hansen, et al, (2013), Hansen, et al, (2010), Lambert, et al, (2010), Scott, et al, (2012 Santarelli, et al, (2011), Wong, et al, (2013 Associated with Scz as revealed by higher serum level in sporadic patients Shi, et al, (2012) Mellios, et al, (2009) Associated with Scz as revealed by higher serum level in sporadic patients Shi, et al, (2012) Cheng, et al, (2007) and Qurashi and Jin, 2010). This review will discuss recent progress on understanding the roles of miRNAs in normal brain development and the association of these miRNAs with neurodevelopmental diseases, specifically schizophrenia and bipolar disorder, two closely related disorders (Table 1).…”
Section: Camkiiγmentioning
confidence: 97%
“…This suggests that these miRNAs may be induced in response to hyperglycaemia and hyperlipidaemia, two conditions typically encountered in prediabetic and diabetic states. In neurons, the expression of miR-132 is triggered following activation of the cAMP-dependent pathway and of the transcription factor cAMP response element-binding protein (CREB) [35][36][37][38][39][40]. Incubation of rat insulinoma INS-1 832/13 cells with cAMP-raising agents has been shown to cause a rapid increase in the miR-132 precursor [41], indicating that a similar regulatory mechanism may also operate in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive spine growth might be one of the side-effects of transgenic miR-132 overexpression that might limit the functional working range of neurons [62]. Similarly, viral overexpression of miR-132 in the perirhinal cortex abolished novel object recognition memory when tested 20 min, but not 24 h after the training session [63]. Long-term plasticity, both LTP and LTD, in the perirhinal cortex is also reduced in the presence of abnormally high levels of miR-132 [63].…”
Section: (I) Mir-132mentioning
confidence: 99%